Konsep Manusia dalam Perspektif Falsafah Pendidikan Islam : Human Concepts from the Perspective of Islamic Education Philosophy - Abi Pradana; Vera Dwi Saputri; Awalia Rindu Az Zahra (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2026)
This paper discusses how human beings are understood in the perspective of Islamic Philosophy of Education. It explains that humans are created by Allah with both physical and spiritual potentials. In other words, humans are not only physical beings, but also possess intellect, heart, and moral responsibility. From God’s perspective, humans have an important role as servants of Allah and as khalifah (vicegerents) on earth, responsible for maintaining and managing the world in a proper way. Meanwhile, in Islamic Philosophy of Education, nature is seen as a source of learning, humans as the main actors in the educational process, and knowledge as a tool to develop the innate potential (fitrah) that every person is born with. Through Islamic education, humans are expected to grow into balanced individuals intellectually capable, spiritually strong, and morally upright so that they can fulfill their responsibilities in life wisely and responsibly.